Specialized Discourses and Their Readerships - Banks, David; Di Martino, Emilia (The M.A.K. Halliday Library Functional Linguistics Series, 2019)
This volume studies the relationship between the writers of specialized text and their readers in a broad range of settings, including research, popularization and education. It offers younger researchers an insight into the targeting process, helping them consider the impact their work can have, and showing them how to achieve greater exposure. Further, it offers an invaluable reflective instrument for beginning and experienced researchers, drawing on a veritable treasure trove of their colleagues' experience. As such, it represents a way for researchers and students in linguistics and related disciplines to access issues from a different, insider perspective. Reader targeting has become a very sophisticated process, with authors often addressing their potential readers even in video. Compared to other forms of writing, academic writing stands out because authors are, in the majority of cases, also consumers of the same type of products, which makes themexcellent "targeters." .